Specific Antibodies to Porphyromonas gingivalis Lys-Gingipain by DNA Vaccination Inhibit Bacterial Binding to Hemoglobin and Protect Mice from Infection - Kuboniwa, Masae (American Society for Microbiology, 2001)
Lys-gingipain (KGP), a lysine-specific cysteine proteinase, is one of the major virulence factors of Porphyromonas gingivalis. Here we examined the involvement of the catalytic domain of KGP (KGP(cd)) in hemoglobin binding by P. gingivalis, using a specific immunoglobulin G (IgG) elicited by the administration of plasmid DNA encoding KGP(cd) or the catalytic domain of Arg-gingipain (RGP(cd)). The pSeq2A/kgp(cd) and pSeq2B/rgp(cd) plasmids were constructed by the ligation of kgp(cd) and rgp(cd) DNA fragments, respectively. Female BALB/c mice were immunized with each of these plasmids. pSeq2A/kgp(cd) elicited a strong response to recombinant KGP(cd) (rKGP(cd)), as well as to comparably produced rRGP(cd)-reactive antibodies. The serum antibodies elicited by pSecTag2B/rgp(cd) also cross-reacted with rKGP(cd) as well as rRGP(cd). Anti-KGP(cd) IgG significantly inhibited hemoglobin binding by P. gingivalis. Furthermore, the inhibition of hemoglobin binding was markedly enhanced by a combination of anti-KGP(cd) and anti-fimbriae. Anti-RGP(cd) IgG showed a negligible inhibitory effect, while both anti-KGP(cd) and anti-RGP(cd) IgGs showed significant inhibitory effects on Lys- and Arg-specific proteolytic activities and on the growth of P. gingivalis under iron-restricted conditions where supplemented hemoglobin was the sole iron source. Immunized mice were challenged by intraperitoneal inoculation with P. gingivalis. All nonimmunized mice died within 72 h; however, vaccination with pSeq2A/kgp(cd) and pSeq2B/rgp(cd) prevented inflammatory responses and prolonged the survival rate of immunized mice by 43 and 27%, respectively. These results suggest that KGP(cd) acts as a hemoglobin-binding protein and can also be useful as an immunogen inducing a protective response to P. gingivalis infection.